2017
DOI: 10.1016/j.concog.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating cues in mind wandering: Verbal cues affect the frequency and the temporal focus of mind wandering

Abstract: Our understanding of mind wandering (MW) has dramatically increased over the past decade. A key challenge still facing research is the identification of the processes and events that directly cause and control its occurrence. In the present study we sought to shed light on this question, by investigating the effects of verbal cues on the frequency and temporal focus of MW. To this aim, we experimentally manipulated the presence of irrelevant verbal cues during a vigilance task, in two independent groups (Verba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 58 publications
(82 reference statements)
10
54
0
Order By: Relevance
“…Several recent studies have shown that MW is a cue-dependent phenomenon, triggered by both internal and external events. Specifically, there is evidence that both task-irrelevant and task-relevant external stimuli [7][8][9][10][11]13] might act as triggers for MW episodes. In a recent study, Pelagatti et al [21] found a significantly larger pupil dilation following cue-words reported by participants as the trigger of MW compared to non-trigger words (with similar emotional content), and the pupil dilation appeared to increase over time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several recent studies have shown that MW is a cue-dependent phenomenon, triggered by both internal and external events. Specifically, there is evidence that both task-irrelevant and task-relevant external stimuli [7][8][9][10][11]13] might act as triggers for MW episodes. In a recent study, Pelagatti et al [21] found a significantly larger pupil dilation following cue-words reported by participants as the trigger of MW compared to non-trigger words (with similar emotional content), and the pupil dilation appeared to increase over time.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained with this vigilance task revealed that (i) the majority of recorded MW episodes are reported as being triggered by the task-irrelevant verbal cues, (ii) the exposure to verbal cues may affect the temporal orientation of MW, increasing the proportion of past-oriented MW [11,13]. However, one of the limitations of these studies is that MW triggers are identified by introspective measures, i.e.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations